Vascular Surgical Emergencies: How will Future Surgeons be Trained? - Richards, T (The Royal College of Surgeons of England, 2006)
INTRODUCTION: We wished to assess whether pattern and impact of emergency vascular surgical referrals has altered since a previous study in 1990. Following introduction of shift working patterns, we wished to assess how these changes may affect vascular training and vascular on-call cover. PATIENTS AND METHODS: Prospective survey of emergency vascular referrals at two district general hospitals (DGH-R and DGH-L) in 2003. DGH-R received only regional referrals whereas DGH-L also received ‘next day’ referrals from a smaller hospital. Results were compared between centres and with a previous study undertaken at DGH-R in 1990. RESULTS: From 1990 to 2003 emergency vascular referrals at DGH-R increased by 51% (53 to 80). The number seen at DGH-R and DGH-L were similar in 2003. There were significantly more out-of-hours referrals in DGH-R than DGH-L (59% versus 35%; P = 0.0123). Referrals were more likely to be seen initially by the vascular team at DGH-L than DGH-R (80% versus 47%, P < 0.0001). CONCLUSIONS: Vascular emergency referrals have increased. A trainee was likely to see more emergency referrals at DGH-L than DGH-R. This may impact on future training.